FRI0315 GENDER DIFFERENCES IN PATIENT JOURNEY TO DIAGNOSIS AND PATIENT-REPORTED OUTCOMES: RESULTS FROM THE EUROPEAN MAP OF AXIAL SPONDYLOARTHRITIS (EMAS). (2nd June 2020) - Garrido-Cumbrera, M.; Poddubnyy, D.; Gossec, L.; Mahapatra, R.; Bundy, C.; Makri, S.; Sanz-Gómez, S.; Christen, L.; Delgado-Domínguez, C. J.; Navarro-Compán, V.
Abstract : Background: Growing evidence of similarities in male-female prevalence of axial spondyloarthritis (axSpA) has stimulated the need to evaluate gender differences in patient experiences. Objectives: To evaluate gender differences in diagnostic journey, disease-characteristics and patient-reported outcomes (PROs) in axSpA patients. Methods: Data from 2846 unselected patients of the European Map of Axial Spondyloarthritis (EMAS) through an online survey (2017-2018) across 13 countries were analysed. Socio-demographic characteristics, diagnosis, disease-characteristics, and PROs [BASDAI (0-10), spinal stiffness (3-12), functional limitation (0-54) and psychological distress (0-12, GHQ-12)] were compared between genders. Χ 2 (for categorical variables) and student-t (for continuous variables) were employed. Results: 1, 746 (61.3%) females participated in the EMAS, with homogeneous gender distribution across most countries (Fig 1 ). Compared to males, females reported longer diagnostic delay (6.1±7.4 vs 8.2±8.9; p<0.001), more visits to physiotherapists (34.5% vs 49.5%; p<0.001) and osteopaths (13.3% vs 24.4%; p<0.001) before being diagnosed (Table 1 ), higher disease activity in all BASDAI items and greater functional limitation, psychological distress and self-reported anxiety and depression (Table 2 ). Conclusion: Important gender differences are observed in axSpA such as a longer patient journey to diagnosis, poorer PROs, and greater psychological burden in females. These results point to unmet needs in females with axSpA, requiring particular attention. Acknowledgments: Funded by Novartis Pharma AG Disclosure of Interests: Marco Garrido-Cumbrera: None declared, Denis Poddubnyy Grant/research support from: AbbVie, MSD, Novartis, and Pfizer, Consultant of: AbbVie, Bristol-Myers Squibb, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB, Speakers bureau: AbbVie, Bristol-Myers Squibb, Eli Lilly, MSD, Novartis, Pfizer, Roche, UCB, Laure Gossec Grant/research support from: Lilly, Mylan, Pfizer, Sandoz, Consultant of: AbbVie, Amgen, Biogen, Celgene, Janssen, Lilly, Novartis, Pfizer, Sandoz, Sanofi-Aventis, UCB, Raj Mahapatra: None declared, Christine Bundy Grant/research support from: Has received unrelated honoraria from Abbvie, Celgene, Janssen, Lilly, Novartis, and Pfizer., Souzi Makri: None declared, Sergio Sanz-Gómez: None declared, Laura Christen: None declared, Carlos Jesús Delgado-Domínguez: None declared, Victoria Navarro-Compán Consultant of: Abbvie, Lilly, Novartis, Pfizer, UCB, Speakers bureau: AbbVie, MSD, Lilly, Novartis, Pfizer, UCB